Chiral Property of Field Galaxies Around the Local Supercluster - Aryal, Binil (Scientific World, 2010)
We present an analysis of the winding sense of 1,621 field galaxies having radial velocity 3 000 km/s to 5,000 km/s. The arm patterns (S and Z-shaped, i.e., chiral property) of the spirals are visually studied. In order to classify the structural modes of spirals, we assume a random direction of the rotation of galaxies. Anisotropy in the chiral symmetry and the preferred alignment of galaxies is studied using chi-square, auto-correlation and the Fourier tests. We noticed a good agreement between the random alignment of the position angle (PA) distribution and the existence of chirality in both the leading and trailing modes. Chirality is found stronger for the late- type spirals (Sc, Scd, Sd and Sm) than that of the early types (Sa, Sab, Sb and Sbc). A significant dominance (17% & 8.5%) of trailing modes is noticed in the barred spirals. In addition, chirality of field galaxies is found to remain invariant under the global expansion. A random alignment is noticed in the PA-distribution of leading and trailing mode spirals. Key Words: Spiral galaxies; Hubble sequence; Chirality; Clusters: individual (Local Supercluster). DOI: 10.3126/sw.v8i8.3856 Scientific World Vol.8(8) 2010 pp.81-90